Reclamation of Ex-Mining Land for Agricultural Extensification - DARIAH, AI; ABDURACHMAN, A.; SUBARDJA, DJADJA (Jurnal Sumberdaya Lahan, 2010)
Utilization of ex-mining land for agricultural extensification is an opportunity to solve the problem of food and environment. This paper discusses prospective utilization of ex-mining land for agricultural extensification. Mining area equipped with a business license for mining in Indonesia is around 2.2 million ha under Coal Concession Agreement, and 2.9 million ha under the Contract of Effort. A part of land is already finished being mined, and be managed properly in order to benefit the community and not damage the environment. The initial steps that need to be done is mapping of mined lands, included a status of ownership (land tenure), so that subsequent use of both for agriculture and other businesses can be sustainable. Land reclamation is necessary to increase capacity and efficiency for biomass production. Determination of land use types, should be based on land tenure, bio-physical conditions of land, and the needs of the community or local government. In the future, mining land management requirements is not enough simply by opening a feasibility study for mining operations, but need to be accompanied also with itsclosure plan (planning of closures), which includes environmental protection and mitigation of socio-economic problems. This needs to be one of the terms of the granting of mining permits.